The work of nations : preparing ourselves for 21st century capitalism - Reich, Robert B (New York : Vintage Books, 1992)
Examines the socio-economic questions that will be plaguing the policy-makers of the future
Introduction : the national idea -- The origins of economic nationalism -- Economic nationalism and high-volume production -- The corporation and the national interest -- The national champion -- The national bargain -- The presumed problem -- From high volume to high value -- The new web of enterprise -- The diffusion of ownership and control -- The global web -- The end of the national champion -- The coming of irrelevance of corporate nationality -- The perils of vestigial thought -- The three jobs of the future -- A digression on symbolic analysis and market incentive -- American incomes -- Why the rich are getting richer and the poor, poorer -- The education of the symbolic analyst (I) -- The education of the symbolic analyst (II) -- The problem restated -- The decline of public investment -- The uses of vestigial thought -- The new community -- The politics of secession -- Who is'us'? -- Afterword : national identity in a post-Soviet world
Koleksi Sumbangan : Prof. Datuk (Dr. ) Anuwar Ali
Includes bibliographical references and index
Keywords: United States -- Economic conditions -- 1981-2001; Economic forecasting -- United States; Capitalism -- United States; International economic relations; Capitalismo -- Estados Unidos